hPMSCs-Derived Exosomal miRNA-21 Protects Against Aging-Related Oxidative Damage of CD4+ T Cells by Targeting the PTEN/PI3K-Nrf2 Axis - Xiong, Yanlian; Xiong, Yanlei; Zhang, Hengchao; Zhao, Yaxuan; Han, Kaiyue; Zhang, Jiashen; Zhao, Dongmei; Yu, Zhenhai; Geng, Ziran; Wang, Longfei; Wang, Yueming; Luan, Xiying (Frontiers in Immunology, 2021)
Mesenchymal stem cells (MSCs)-derived exosomes were considered a novel therapeutic approach in many aging-related diseases. This study aimed to clarify the protective effects of human placenta MSCs-derived exosomes (hPMSC-Exo) in aging-related CD4+ T cell senescence and identified the underlying mechanisms using a D-gal induced mouse aging model. Senescent T cells were detected SA-β-gal stain. The degree of DNA damage was evaluated by detecting the level of 8-OH-dG. The superoxide dismutase (SOD) and total antioxidant capacity (T-AOC) activities were measured. The expression of aging-related proteins and senescence-associated secretory phenotype (SASP) were detected by Western blot and RT-PCR. We found that hPMSC-Exo treatment markedly decreased oxidative stress damage (ROS and 8-OH-dG), SA-β-gal positive cell number, aging-related protein expression (p53 and γ-H2AX), and SASP expression (IL-6 and OPN) in senescent CD4+ T cells. Additionally, hPMSC-Exo containing miR-21 effectively downregulated the expression of PTEN, increased p-PI3K and p-AKT expression, and Nrf2 nuclear translocation and the expression of downstream target genes (NQO1 and HO-1) in senescent CD4+ T cells. Furthermore, in vitro studies uncovered that hPMSC-Exo attenuated CD4+ T cell senescence by improving the PTEN/PI3K-Nrf2 axis by using the PTEN inhibitor bpV (HOpic). We also validated that PTEN was a target of miR-21 by using a luciferase reporter assay. Collectively, the obtained results suggested that hPMSC-Exo attenuates CD4+ T cells senescence via carrying miRNA-21 and activating PTEN/PI3K-Nrf2 axis mediated exogenous antioxidant defenses.